The effects of intraseasonal oscillations on landfalling tropical cyclones in the Philippines during the boreal summer - Wu, Peicong; Ling, Zheng; He, Hailun (Frontiers in Earth Science, 2023)
This paper investigates the isolated and combined effects of two intraseasonal oscillations, the Madden-Julian oscillation (MJO) and the quasi-biweekly oscillation (QBWO), on landfall of tropical cyclones (TCs) in the Philippines during boreal summer (May-September). The results show that both the MJO and the QBWO can significantly affect the frequency, landfall intensity, location, and translation speed of TCs that make landfall in the Philippines. During the convective (non-convective) phases of the MJO and the QBWO, more (less) frequent and stronger (weaker) TCs make landfall in the Philippines. This is due to the increased (decreased) frequency of TCs formation in the northwestern Pacific (NWP) and environmental factors in the region east of the Philippines that are favorable (unfavorable) for the development of TCs. With the northward propagation of the convective signals of the MJO and QBWO, the Western Pacific Subtropical High (WPSH) shifts eastward, and the steering flow is unfavorable for westward movement of NWP TCs. This, in turn, causes a northward shift in the landfall locations and a decrease in the translation speed of TCs. These results are helpful for the prediction of the TCs affecting the Philippines.